Putting evidence into practice - Hobbs, R (1999)
Heart failure is a common condition associated with substantial mortality, morbidity and impairment of quality of life. However, despite the proven efficacy of angiotensin-converting enzyme (ACE) inhibitors, heart failure is often under-diagnosed and under-treated, particularly in primary care. In some studies, for example, only about one-third of patients received ACE inhibitors, and at doses substantially lower than those shown to be effective in clinical trials. The major reason for under-prescribing ACE inhibitors appears to be that concerns over adverse effects dominate perceptions of treatment benefits. The recent Assessment of Treatment with Lisinopril And Survival (ATLAS) Study, however, has shown that treatment with high doses of lisinopril is associated with a significant reduction in deaths and hospitalizations, without a concomitant increase in the risk of serious adverse events. There is, therefore, evidence for the routine use of maximum-tolerated doses of ACE inhibitors in patients with heart failure treated in primary care. Guidelines for the initiation of such treatment are presented.